Naive and radiolabeled antibodies to E6 and E7 HPV-16 oncoproteins show pronounced antitumor activity in experimental cervical cancer. (July 2015) - Phaëton, R; Gutierrez, J; Jiang, Z; Karabakhtsian, RG; Albanese, J; Sunkara, J; Fisher, DR; Goldberg, GL; Dadachova, E
Background: In spite of profound reduction in incidence, cervical cancer claims >275, 000 lives annually. Previously we demonstrated efficacy and safety of radioimmunotherapy directed at HPV16 E6 oncoprotein in experimental cervical cancer.Materials & methods: We undertook a direct comparison of targeting E7 and E6 oncoproteins with specific 188 Rhenium-labeled monoclonal antibodies in CasKi subcutaneous xenografts of cervical cancer cells in mice.Results: The most significant tumor inhibition was seen in radioimmunotherapy-treated mice, followed by the unlabeled monoclonal antibodies to E6 and E7. No hematological toxicity was observed. Immunohistochemistry suggests that the effect of unlabeled antibodies is C3 complement mediated.Conclusion: We have demonstrated for the first time that radioimmunotherapy directed toward E7 oncoprotein inhibits experimental tumors growth, decreases E7 expression and may offer a novel approach to cervical cancer therapy.